Factors associated with adaptation level in the older adult residential care facilities: a path analysis - Zhao, Di; Niu, Meilan; Zhang, Shanfeng; Shi, Yan; Zhou, Lin; Song, Yuxia; Ma, Rui; Wang, Peng (Frontiers in Public Health, 2023)
Background It has become very common for older adults to relocate to residential care facilities. Yet whether older adults adapt to life in a long-term care residential facility through perception, reflection, and conscious behavioral choices is a challenging social issue. Previous research has shown that adaptation is influenced by physical, mental, psychological, social systems, and other debris factors. However, existing knowledge is often based on unidirectional relationships between these factors and adaptation. Few studies have formally examined bivariate relationships between these factors, and the influence of adaptation between these factors internally remains unclear. Therefore, there is a need to examine the structural causality of adaptation in residential care facilities influenced by a combination of physical, emotional, social and psychological factors, life satisfaction, and social support. Methods The present cross-sectional study recruited older adults from three residential care facilities in Henan province, China, through convenience sampling. The Chinese Nursing Home Adjustment Scale (NHAS), Geriatric Depression Scale-15 (GDS-15) and Social Support Scale (SSRS), Satisfaction with Life Scale (SWLS), and Barthel Index were employed to measure the older adult’ adjustment level, depression level, social support, satisfaction with life, and self-care ability of the BMC, respectively. The relationships between depression, social support, self-care, satisfaction with life, and adaptation were analyzed and a structural equation model was developed. Results A total of 210 participants completed the questionnaire. The model demonstrated an acceptable fit of the data. The results showed that the difference between life satisfaction and depression on the level of adaptation was 60 and 23%, respectively. Social support and life satisfaction had a positive direct effect on the level of adaptation, both showing a positive correlation with the level of adaptation. Depression, on the other hand, have a direct effect on the level of adaptation and showed a negative correlation with the level of adaptation. Self-care ability indirectly influenced adaptation mediated by social support. Conclusion Social support has a positive impact on both life satisfaction and depression, which in turn promotes adaptation. As a major source of social support, family members and nursing home staff in residential care facilities can enhance social support for older people through improved interaction, which can have a meaningful and positive impact on levels of adjustment. The model demonstrates the strengthening and weakening of social support, self-care, life satisfaction, and depression levels, which can help inform the development of relevant care health strategies for older people to promote levels of adjustment and improve quality of life.